Maprotiline inhibits LPS-induced expression of adhesion molecules (ICAM-1 and VCAM-1) in human endothelial cells - Laleh Rafiee; Valiollah Hajhashemi; Shaghayegh Haghjooy Javanmard (Wolters Kluwer Medknow Publications, 2016)
Regardless of the known anti-inflammatory potential of heterocyclic antidepressants, the mechanisms concerning their modulating effects are not completely known. In our earlier work, maprotiline, a heterocyclic antidepressants, considerably inhibited infiltration of polymorphonuclear cell leucocytes into the inflamed paw . To understand the mechanism involved, we evaluated the effect of vascular cell adhesion molecule (VCAM-1), intracellular adhesion molecule (ICAM-1) expression in stimulated endothelial cells. Endothelial cells were stimulated with lipopolysaccharide (LPS) in the presence and absence of maprotiline (10 -8 to 10 -6 M) and ICAM-1 and VCAM-1 expression were measured using real-time quantitative reverse transcription polymerase chain reaction. Maprotiline significantly decreased the LPS-induced expression of VCAM-1 at all applied concentrations. The expression of ICAM-1 decreased in the presence of maprotiline at 10 -6 M concentration (P<0.05). Since maprotiline inhibits the expression of adhesion molecules, ICAM-1 and VCAM-1 in LPS-stimulated human endothelial cells , it can be a possible way through which maprotiline exerts its anti-inflammatory properties.